Superdiversity, policy and governance in Europe : multi-scalar perspectives - Phillimore, Jenny (New perspectives in policy & politics., 2020)
First published as a special issue of Policy & Politics, this insightful volume brings together contributions from experts across Europe to explore the ways in which superdiversity has influenced the development of policy and to consider challenges for the future.